Measurement of Loss Aversion Behavior Under Prospect Theory: Comparison of Various Kinds of Individuals - Wang, Mu-Lan; Huang, Hung-Hsi; Ho, Shu-Hui (Indian Journal of Finance, 2013)
This paper designs a binary prospect questionnaire according to previous literature for extracting the certainty equivalents of gains and losses prospects. Individual utility function is defined by the power utility function, in which the gain power parameter and loss power parameter are estimated by the least squares method. The respondents for the present study comprised of 20 common people, 20 MBA students, and 20 financial workers, and the main findings are as follows. First, individuals revealed risk averse attributes for gains and losses, but the risk averse magnitude for gains was larger than it was for losses. Second, the individual utility function is likely concave. Third, relative to others, the financial workers were less loss averse. Finally, women were generally more loss averse than men.